Serum Protein N-Glycosylation Signatures of Neuroblastoma - Qin, Wenjun; Pei, Hao; Li, Xiaobing; Li, Jia; Yao, Xuelian; Zhang, Rufang (Frontiers in Oncology, 2021)
Background Neuroblastoma is the most common extracranial childhood solid tumor which accounts for 10% of the malignancies and 15% of the cancer fatalities in children. N-glycosylation is one of the most frequent post-translation protein modification playing a vital role in numerous cancers. N-glycosylation changes in neuroblastoma patient serum have not been studied in existing reports. The comprehensive analyses of serum N-glycomics in neuroblastoma can provide useful information of potential disease biomarkers and new insights of the pathophysiology in neuroblastoma. Methods The total serum protein N-glycosylation was analyzed in 33 neuroblastoma patients and 40 age- and sex-matched non-malignant controls. N-glycans were enzymatically released, derivatized to discriminate linkage-specific sialic acid, purified by HILIC-SPE, and identified by MALDI-TOF-MS. Peak areas were acquired by the software of MALDI-MS sample acquisition, processed and analyzed by the software of Progenesis MALDI. Results Three glyco-subclasses and six individual N-glycans were significantly changed in neuroblastoma patients compared with controls. The decreased levels of high mannose N-glycans, hybrid N-glycans, and increased levels of α2,3-sialylated N-glycans, multi-branched sialylated N-glycans were observed in neuroblastoma patients. what is more, a glycan panel combining those six individual N-glycans showed a strong discrimination performance, with an AUC value of 0.8477. Conclusions This study provides new insights into N-glycosylation characteristics in neuroblastoma patient serum. The analyses of total serum protein N-glycosylation could discriminate neuroblastoma patients from non-malignant controls. The alterations of the N-glycomics may play a suggestive role for neuroblastoma diagnosis and advance our understanding of the pathophysiology in neuroblastoma.